Great Power Politics and the Struggle over Austria, 1945-1955 - Cronin, Audrey Kurth (Cornell Studies in Security Affairs, 2019)
By virtue of its geographical and historical position, postwar Austria was condemned to a prominent role in the plans of both the East and the West. In this account of an unusual episode in the Cold War, Audrey Kurth Cronin examines the negotiations over Austria and the Soviet Union's sudden and surprising decision to withdraw its troops and accept the country as a neutral Western state, after having rejected any settlement for eight years. Drawing on a wealth of recently declassified British and American documents and on interviews with key Austrian participants, Cronin analyzes the events leading up to the 1955 Austrian State Treaty and, in the process, strengthens our understanding of current East-West relations. Her account of the creation of a neutral state in the heart of a divided Europe will be important reading for all who are concerned with security affairs, international relations, and the history of the Cold War.